Smyd1 is essential for myosin expression and sarcomere organization in craniofacial, extraocular, and cardiac muscles. (20th March 2021) - Jiao, Shuang; Xu, Rui; Du, Shaojun
Abstract: Skeletal and cardiac muscles are striated myofibers that contain highly organized sarcomeres for muscle contraction. Recent studies revealed that Smyd1, a lysine methyltransferase, plays a key role in sarcomere assembly in heart and trunk skeletal muscles. However, Smyd1 expression and function in craniofacial muscles are not known. Here, we analyze the developmental expression and function of two smyd1 paralogous genes, smyd1a and smyd1b, in craniofacial and cardiac muscles of zebrafish embryos. Our data show that loss of smyd1a ( smyd1a mb5 ) or smyd1b ( smyd1b sa15678 ) has no visible effects on myogenic commitment and expression of myod and myosin heavy-chain mRNA transcripts in craniofacial muscles. However, myosin heavy-chain protein accumulation and sarcomere organization are dramatically reduced in smyd1b sa15678 single mutant, and almost completely diminish in smyd1a mb5 ; smyd1b sa15678 double mutant, but not in smyd1a mb5 mutant. Similar defects are also observed in cardiac muscles of smyd1b sa15678 mutant. Defective craniofacial and cardiac muscle formation is associated with an upregulation of hsp90α1 and unc45b mRNA expression in smyd1b sa15678 and smyd1a mb5 ; smyd1b sa15678 mutants. Together, our studies indicate that Smyd1b, but not Smyd1a, plays a key role in myosin heavy-chain protein expression and sarcomere organization in craniofacial and cardiac muscles. Loss of smyd1b results in muscle-specific stress response.